2015
DOI: 10.1542/peds.2015-0749
|View full text |Cite|
|
Sign up to set email alerts
|

Safety of Botulinum Toxin Type A for Children With Nonambulatory Cerebral Palsy

Abstract: To determine safety of intramuscular botulinum toxin A (BoNT-A) injections to reduce spasticity and improve care and comfort of nonambulatory children with cerebral palsy (CP).METHODS: Nonambulatory children with CP were randomly allocated to receive either BoNT-A (n = 23) or sham procedure (n = 18) in Cycle 1. In Cycle 2, the BoNT-A group received a second episode of BoNT-A (n = 20) and sham group received their first episode of BoNT-A (n = 17). A pediatric rehabilitation specialist masked to group allocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
1
21
0
1
Order By: Relevance
“…24 A recent randomized controlled trial reported similar rates of moderate-to-severe adverse events in both BoNT-A treatment and placebo arms. 25 What we have described in this study is a temporal association between BoNT-A injections and adverse events. For some adverse events (perhaps many) this relationship may also be causative; for others, they may be related to the comorbidities and poor health associated with severe CP and unrelated to BoNT-A injections.…”
Section: Discussionmentioning
confidence: 52%
“…24 A recent randomized controlled trial reported similar rates of moderate-to-severe adverse events in both BoNT-A treatment and placebo arms. 25 What we have described in this study is a temporal association between BoNT-A injections and adverse events. For some adverse events (perhaps many) this relationship may also be causative; for others, they may be related to the comorbidities and poor health associated with severe CP and unrelated to BoNT-A injections.…”
Section: Discussionmentioning
confidence: 52%
“…17 Increasing dose (units/kg) has also been suggested to be associated with increased emergency department presentations. 17 Gastrostomy has also been suggested to be associated with more severe adverse events in a study of children in GMFCS levels IV and V. 12 We acknowledge the considerable overlap between those children with dysphagia and those with a gastrostomy.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have been published that support decisionmaking in this area. Total adverse events after BoNT-A have been reported to occur in 3.3% to 56% of injection episodes, [11][12][13][14][15] reflecting different study designs. Adverse events with symptoms suggesting systemic spread are less common, 16 estimated to occur in 1% to 2.2% of injection episodes.…”
mentioning
confidence: 99%
“…Commonly reported side and adverse effects are fatigue, flu-like symptoms, swallowing difficulties, increased seizures and bladder and bowel incontinence. [45][46][47][48][49][50][51][52] These are usually transient. No increased risk is reported between one and two episodes of BoNT.…”
Section: Dosagementioning
confidence: 99%